ANALYSIS OF MARINE ZONE MANAGEMENT IN DISPUTED ISLAND TERRITORIES - Khomsin, Khomsin; Pratomo, Danar Guruh; Zahra, Ayu Isnania (UI Scholars Hub, 2023)
Indonesia has 17,204 islands registered, named, and coordinated by Geospatial Information Agency (BIG). The number of islands can threaten maritime boundary disputes between provinces, districts, and cities. One of the disputes is the claim over Pulau Tujuh, which is mutually contested for ownership by the Province of Bangka Belitung and the Province of Riau Islands. This study aims to analyze the marine management zone of the Pulau Tujuh claim. It is carried out using the cartometric method. This study of regional boundaries refers to the Regulation of The Minister of Home Affairs of The Republic of Indonesia 141 of 2017, where the withdrawal of sea boundaries uses a normal baseline. A province can claim 12 nautical miles of maximum sea area. Furthermore, the boundary is drawn using the median line principle if two areas face each other fewer than 24 nautical miles. Three scenarios determine marine management zones: Pulau Tujuh is status quo, Pulau Tujuh is included in Bangka Belitung and Riau Islands. The first scenario shows that the marine management zone of the Bangka Belitung has an area of 37,157.84 km2, and the Riau Islands have an area of 92,853.55 km2. The second scenario results in Bangka Belitung having 39,644.96 km2. In the last scenario, Riau Islands has an area of 95,340.67 km2 maritime management zone. Pulau Tujuh does not significantly influence the marine management zone of each province, whereas Bangka Belitung (6.27%) and Riau Islands (2.61%). General allocation funds or Dana Alokasi Umum (DAU) increase would be 3.36% for Bangka Belitung and 2.25% for Riau Islands if Pulau Tujuh included Rp 22,800,736,812. This result implies that each province wants to defend its argument that Pulau Tujuh falls under its administrative territory.